Automated control of boiler plant energy-seving technologies - Palchik, Oleg; Levchenko, Alexander (My University, 2013)
The problem of energy savings using automated monitoring and control.
Keywords: energy saving; boiler plant; automatic; system optimization; енергозбереження; котельна установка; автоматика; оптимізація системи; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка